Uptake of Seeds Secondary Metabolites by Virola surinamensis Seedlings - Massuo Jorge Kato; Massayoshi Yoshida; Norberto Peporine Lopes; Denise Brentan da Silva; Alberto José Cavalheiro (International Journal of Analytical Chemistry)
The major secondary metabolites and fatty acids occurring in the seeds of Virola surinamensis were monitored by GC-MS during germination and seedling development. The role as carbon source for seedling development was indicated considering that both classes of compounds were similarly consumed in the seeds and that no selective consumption of compounds could be detected.